ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN SISTEM INFORMASI AKUNTANSI - Trisna Savitri, Ni Made; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2015)
The aim of this research was to determine the effect of performance expectancy, effort expectancy, social factors, facilitating conditions and complexity of the task on interest of usage of information system . The respondents of the research are accountant at budget hotel in Denpasar. Data has gathered by questionnaires and 66 questionnaires have sent to budget hotel, 59 questionnaires were returned and can be used. The data were analyzed by using multiple regression by SPSS 16 software. The results showed that the performance expectancy, effort expectancy, social factors, facilitating conditions, and the complexity of the task are significant positive influence to interest of usage of information system .
Keywords: Performance Expectancy, Effort Expectancy, Social Factors, Facilitating Conditions, Complexity of the Task